A Parallel Multiscale Simulation Framework for Complex Polymerization: AB2‐Type Monomer Hyperbranched Polymerization as an Example. Issue 2 (28th September 2018) - Zhang, Zidan; Krajniak, Jakub; Samaey, Giovanni; Nies, Erik
Abstract: A multiscale simulation framework for polycondensation and other types of polymerization mechanisms, which is used to study the hyperbranched polymerization of AB2 type monomer 4, 4‐bis‐(4'‐hydroxyphenyl)pentanoic acid is presented. The reaction framework is established by combining the coarse‐grained molecular dynamics and the reactive Monte Carlo method, in which the coarse‐grained molecular dynamics handles the diffusion of particles and the reactive Monte Carlo method determines the bond formation. The influence of parameters in the simulation model on the quality of the simulation results is explicitly evaluated. Specific guidelines on how to choose proper values for the simulation model parameters are given here. It is shown that i) the reaction interval should be chosen from the ballistic region of the diffusion profile; and ii) the first valley of the radial distribution function of reactants is a good value for the reaction capture radius for polycondensation in terms of accuracy of the calculations. Moreover, a recipe to determine the rate constant from the kinetic equation is explicitly proposed. Using the guidelines, excellent agreement between simulation results and the experimental data is obtained. Abstract : The parallel multiscale simulation framework presented here can be used not only to investigate the polymerization process at the coarse‐grained level, but also to study the formed materials at the atomistic level. For instance, polymer structures can be first constructed at the coarse‐grained level, after which multiple polymer properties can be studied based on the reverse mapped structures.